Pengolahan Air Limbah Tempe dengan Metode Sequencing Batch Reactor Skala Laboratorium dan Industri Kecil Tempe - Winda Winda (Seminar Nasional Teknik Kimia Kejuangan, 2015)
Tempe industries have been known, and implemented at industries scale but those tempe industries are not yet fully completed with waste water treatment plant. The purpose of this research is to study sequencing batch reactor (SBR) and determination of flow rate, stirring speed, and concentration of inoculum to give the biological of oxygen demand (BOD) of the processed wastewater according to the SNI. The benefits of this research is to introduce SBR as an alternative for industrial tempe. The method consists of charging, chemical reactions, precipitation, disposal, and stabilization followed by flow rate, inoculum concentration and agitation speed. In the preliminary experiment, the flow rate for the wastewater treatment was investigated (3 L/h, 4.2 L/h, and 5 L/h) to the BOD. The main experiments were conducted to observe the effect of mixing (variation of 50 rpm, 100 rpm, and 150 rpm) and the effect of inoculum (variation of 5%, 10%, and 15%) to the BOD. Chemical analyses was done in term such as BOD and pH which followed by analyses TSS, TDS, COD. Results obtained in this research are interaction between stirring speed and concentration of inoculums can influence the yield of treatment. After addition of 10% inoculums, stirring speed of 100 rpm, the BOD was decreased to 218,4 ppm and after the tertier treatment, BOD decreased to 93,6 ppm.